Temporal presence of Indo-Pacific humpback dolphins to the piling during the first offshore wind farm construction in the Pearl River Estuary, China - Fang, Liang; Wu, Yuping; Pine, Matthew K.; Wang, Xinxing; Chen, Tao (Frontiers in Marine Science, 2025)
The Guishan Offshore Wind Farm is the first offshore wind power facility located within the habitat of Indo-Pacific humpback dolphins (Sousa chinensis) in Guangdong province of China. To assess the Indo-Pacific humpback dolphin’s response to wind farm construction, this study deployed a broadband passive acoustic monitoring system to investigate the acoustic behavior of humpback dolphins during pile driving activities. Results indicate that Indo-Pacific dolphins were acoustically detected at the wind farm site both pre-construction and during construction in an area previously identified to provide critical habitat to this population. However, temporal presence patterns differed compared to previous studies. While multiple environmental factors influence the habitat selection of Indo-Pacific dolphins, the result from this study confirmed that Indo-Pacific dolphins altered their occurrence following construction initiation. Pile driving exhibited a minor adverse effect on dolphin presence, though statistically insignificant. This persistence may stem from the area's ecological importance as a core habitat, compelling the dolphins to continue utilizing these waters despite construction disturbances. These findings enhance the understanding of marine engineering impacts on marine mammal habitat ecology and provide a scientific basis for formulating habitat conservation strategies and management measures.